Sandplay : silent workshop of the psyche - Bradway, Kay, 1910- (Routledge, 1997)
Sandplay is a growing field of interest for Jungian and other psychotherapists. This volume provides an introduction to sandplay as well as material for those already using this form of therapy. Based on the authors' clinical work, it includes in-depth sandplay case history material from a wide range of adults and children, detailed notes on interpretation of sand trays and examination of symbols and concepts used in sandplay. The text also provides historical background for understanding sandplay as well as discussion of how it works in a clinical context.